Unravelling Motivation: The Key Mediator between Organizational Commitment and Employee Performance at Wyndham Opi Hotel: - Febriani, Yunita; Puspita Sari , Yulia; Fitantina; Ardi Wiyanto, Eko (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This study aims to analyse the role of motivation as a mediator in the relationship between organizational commitment and employee performance at Wyndham Opi Hotel Palembang. The research is based on the phenomenon of the hotel's failure to achieve its specified targets and the relatively high employee turnover rate. Design/methodology/approach: The study was conducted on a population of 150 employees, with data collected through interviews and questionnaires. The analysis technique employed was Structural Equation Modelling-Partial Least Squares (SEM-PLS) to assess the relationships between affective, continuous, and normative commitments, motivation, and employee performance. Research Findings: The findings indicate that affective, continuous, and normative commitments significantly influence employee motivation. However, when examining their direct impact on employee performance, only normative commitment was found to have a significant effect, whereas affective and continuous commitments did not. Furthermore, motivation was found to significantly mediate the relationship between affective and normative commitment to employee performance but not for continuous commitment. These results explain the persistent high turnover rate at Wyndham Opi Hotel Palembang and highlight the need for better hotel management strategies to strengthen employee commitment and reduce turnover. Theoretical Contribution/Originality: This study contributes to the existing literature by providing empirical evidence on the mediating role of motivation in the relationship between organizational commitment and employee performance. It emphasizes the need for organizations to enhance normative commitment and employee motivation to improve performance and reduce turnover, particularly in the hospitality industry